A flight of arrows [large type] - Benton, Lori (Benton, Lori. Pathfinders series, 2016)
"As the Revolutionary War penetrates the Mohawk Valley, two families separated by culture but united by love and faith must find a way to reclaim the son marching toward them in the ranks of their enemies"--